(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Kamala Markandaya is one of the finest and mostdistinguish Indian novelist in English of the post-colonial era who isinternationally recognized for her master piece ‘Nectar in a Sieve’ publishedin 1954. She has achieved a world-wide distinction bywinning Asian Prize for her literary achievement in 1974. Endawed with strong Indian Sensibility, shedepicts women’s issues and problems very deeply in her novels. She explores and interprets the emotionalreactions and spiritual responses of women and their predicament withsympathetic understanding.